Philo of Alexandria : a thinker in the Jewish diaspora - Hadas-Lebel, Mireille. (Studies in Philo of Alexandria, 2012)
Philo (20BCE?-45CE?) is the most illustrious son of Alexandrian Jewry and the first major scholar to combine a deep Jewish learning with Greek philosophy. His unique allegorical exegesis of the Greek Bible was to have a profound influence on the early fathers of the Church. Philo was, above all, a philosopher, but he was also intensely practical in his defence of the Jewish faith and law in general, and that of Alexandria's embattled Jewish community in particular. A famous example was his leadership of a perilous mission to plead the community's cause to Emperor Caligula. This monograph provides a guide to Philo's life, his thought and his action, as well as his continuing influence on theological and philosophical thought.